2D Motions Response Analysis of Floating Offshore Wind Turbine with Various Barge Shapes - Mahmuddin Faisal; Putra Nurhalim Dwi; Klara Syerly (E3S Web of Conferences)
Indonesia has the potential to develop floating wind turbines at sea. Therefore, its movement response needs to be analyzed to ensure that the turbine works properly. This research aims to determine the floating offshore wind turbine barge’s movement response with different floater shapes to regular waves from three different directions (0°, 45°, 90°). The movement response of the floating wind turbine was analyzed using the diffraction and radiation analysis methods in Ansys Aqwa. The research results include the RAO curve for the structure in a couple of two degrees of freedom (heave-pitch) combined with 2-dimensional analyses. The motion response of the floater cube has a maximum value heave motion 0.999 m/m and pitch motion 2.228 °/m, and, the cylindrical shape has a heave motion 1.132 m/m and pitch 10.050 °/m. Lastly, the octagonal has a heave motion 1.010 m/m and pitch 2.565 °/m. The shape and volume of each model affect the response value obtained. The simulation results in this paper can provide considerations in selecting the right floater shape to be used as a wind turbine floater foundation.